Enhancing Communication Between Dental Laboratories and Clinics: The Role of Information Technology Systems in a Developing Country - Nusairat, Farid; Al-Shogran, Salam; Almortadi, Noor; Alzoubi, Karem (Clinical, cosmetic and investigational dentistry, 2024)
Despite the great effort between the dentist and dental technician in prosthesis fabrication, there is a lack of proper communication. According to the laboratory prescription, the communication process must include all the essential elements to complete the prosthesis fabrication correctly. The digital revolution in dentistry suggested using information technology system prescriptions instead of traditional prescriptions. To explore the association between the application of ITS and the communication process between dental laboratories and dental clinics in a developing country setting. The current study used a quasi-experimental design (posttest only). A convenience sample of 600 subjects was divided into two subsamples of 300 subjects each. The data from the first subsample was collected from traditional (paper-based) prescriptions, and the data from the second subsample was collected from the Information Technology System (ITS). It was associated with a statistically significant commitment to recording the most essential information in the dental lab prescription. The time spent completing and delivering the work was faster, and the need for recommunication was less common among those using ITS than those using traditional systems. Regarding the quality of the prosthesis, the need for modification or redo due to improper shade, inappropriate charting of teeth, or lack of additional information in the dental lab prescription was less among users of the ITS system compared to the traditional system (P < 0.05). Using ITS instead of a traditional system can enhance the communication process and the amount filled in the laboratory prescription in multiple aspects, including the completeness of essential information in the dental lab prescription, the time needed to complete the cases, the need to re-communicate less frequently with the dentist, and improved the quality of the prosthesis.